Médio Curso da Bacia do Rio Jacuípe, Bahia: Proposta Metodológica para estimativa de susceptibilidade à degradação ambiental - Silva, Oriana Araujo da (2010)
Currently the changes imposed to landscapes are faster and more intense in several places of the planet due mainly to the appearing and the use of new techniques and machines which transform them into artificial or cultural landscapes. In the medium course of Jacuípe River Basin (JRB) – core area of Brazilian semi-arid region – artificial landscapes are dominant. Such landscapes are result of land cover changes identified in previous research which registered a strong process of anthropization mainly in the form of native vegetation removal by introduction of pastures and urban occupation well as for annual and perennial crups. The elements which constitute the present territorial configuration reflect the historical process of occupation of the landscape discussed in this work whose general aim is the identification of the levels of susceptibility to environmental degradation with the use of integrated analysis of socio-environmental indicators. Due to the geosystemic magnitude of the study area geotechnology tools – specifically the interpretation of satellite imagery and spatial data modeling combined with fuzzy spatial inference – were used in this work. The vegetation cover map – natural or anthropic – produced through supervised classification of Landsat TM5 image (2008) indicated that 74% of the medium course area of JRB do not have any kind of vegetation cover. Thus, with the use of distance maps (buffers) – in order to define the degrees of pertinence of those variables to the fuzzy set of susceptibility to environmental degradation in the medium course of the basin – the work estimated the influence zone of the cities, the roads, and the rivers on the vegetation cover as well as how they are related to types of soil and degrees of slope. After testing different algorithms, the work concluded that fuzzy interpolator (sum) combined more acurately the variables used. That result produced a map with 5 levels of susceptibility to environmental degradation: high, moderately high, intermediate, moderatley low, and low. The work also demonstrated that the medium course of JRB is seriously affected in terms of susceptibility to environmental degradation especially in central area and in the cities of Riachão do Jacuípe, Pé de Serra, Nova Fátima and Gavião. In the towns of São José and Capela, the major concern is the the expansion of the algaroba (Prosopis juliflora). In the cities or towns where the predominant vegetation cover is the sisal (Agave sisalana), the areas which are more susceptible to environmental degradation are located near the venues of municipalities but there is also areas at high risk mainly those related to intensive cattle-raising.